Pemeriksaan Kualitas Air Minum Secara Mikrobiologis di Daerah Bukit Jimbaran - Arie Pradina Putri I Putu Mas (STIKES MUHAMMADIYAH KLATEN, 2021)
The main problem faced in drinking water consumtion is contamination both chemically and biologically. The increasing population in the Bukit Jimbaran area makes demand for drinking water increased. This study was aims to examine the quality of drinking water microbiologically in Bukit Jimbaran area. Research had been carried out in the Laboratory of Microbiology and Virology, Faculty of Mathematics and Natural Science, Udayana University by taking samples from 3 drilled wells and 3 refill drinking water depots randomly. This research was experimental used Most Probable Number (MPN) test for the microbiological of the water that consist of presumptive test using Lactose Broth (LB), confirmative test using Brilliant Green Lactose Broth (BGLB), and complete test using endo jelly media. The result of presumptive test showed two samples of drilled well drinking water and three samples of refill drinking water were positive for Coliform. The result of confirmative test and complete test showed that three refill drinking water samples were positive for Coliform faecal bacteria and E. coli, which showed that the samples were not suitable for consumption